Persalinan Dalam Pandangan Budaya Timor (Atoni) - Dewa Ayu Putu Mariana Kencanawati (JURNAL INFO KESEHATAN, 2018)
The utilization of health facilities in the city of Kupang is very low compared to the national target. Timorese in Kupang City still hold fast and practice some cultural practices related to the life cycle which will influence how Timorese view labor. This study aims to describe labor that is viewed by the Timorese culture (Atoni). This study is a phenomenological research with a qualitative approach, the determination of the sample in this study using purposive sampling technique, data collected through in-depth interviews and thematically analyzed. The results of interviews obtained from childbirth according to Timorese culture are important in the life cycle of women, there are several differences between traditional and modern childbirth treatments including concoctions and delivery positions. Conclusion: Timorese people have their own perception of childbirth, especially in the procedures of childbirth assistance (position and potions) and their perception of childbirth.